Research Paper: Gender Identification With Knee Bicondylar Width and Vertical Diameter of the Femur Head Based on Radiography Assessment - Ghorbanzadeh, Behjat; Soltani, Siamak; Aghakhani, Kamran; Rismantab Sani, Sahar; Ashrafi Esfahani, Shayesteh (International Journal of Medical Toxicology and Forensic Medicine, 2017)
Background: Some skeletal criteria especially for bones of lower limbs are considerably different between men and women that may help in identifying the gender. We studied two lower limbs parameters, i.e. bicondylar width and vertical diameter of the femoral head based on radiographic assessment in gender identification. Methods: Bicondylar width and vertical diameter of the femoral head of 280 radiographs taken from people aged 30 to 75 years were measured. Additionally, gender and age subgroups were recorded and added to the measured anthropometric parameters in the checklist of the study. Results: The mean width of both left and right bicondylar bones as well as vertical diameter of both left and right femoral heads were significantly different between men and women. Considering two parameters of bicondylar width and vertical diameter of femoral head, the measurements could differentiate gender, with 96.7% sensitivity, 72.2% specificity, and 96.0% accuracy. Conclusion: By measuring bicondylar width and vertical diameter of the femur head, it is possible to determine gender with a high discriminative capability.